Role of Ultrasonography in the diagnosis of Chronic liver disease (CLD) and comparison with Laboratory diagnosis (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Chronic liver disease (CLD) is a major hepato biliary problem in day-to-day practice in Bangladesh.Objective: The aim of this study was to assess the efficacy of ultrasonography in the diagnosis of chronic liver disease.Materials and Methods: This cross sectional study was carried out in the Department of Radiology and Imaging of Dhaka National Medical College Hospital during July 2014 to June 2015 for a period of one year. Clinically suspected chronic liver disease (CLD) patients of either sex were recruited as a study population. Patients had history of neoplasm of liver or duration of suffering was less than 6 months were excluded from the study. Initially 72 patients were approached for this study. Among them 58 patients agreed to be the study subjects. Sonography was carried out on these 58 patients but only 50 patients subsequently underwent laboratory investigations or liver biopsy. So, finally 50 patients were included in this study.Results: Out of fifty patients male (58%) were predominant than female (42%). Mean age was 44.3 years (range: 16-65 years) and maximum (44%) patients were found in 36-45 age group. According to the sonographic findings, 18 patients were diagnosed as hepatitis, 16 patients as fatty liver, 12 patients as cirrhosis and 4 as normal. According to the laboratory investigations, finally 11 patients were diagnosed as cirrhosis, 16 patients as fatty liver, 21 patients as hepatitis and 03 patients as normal and 01 patient as storage disease which was not diagnosed by ultrasonography.Conclusion: Ultrasonography is one of the useful diagnostic modality for the diagnosis of chronic liver disease.J. Dhaka National Med. Coll. Hos.  2015; 21  (02): 42-45